1994
DOI: 10.1016/0378-1097(94)90429-4
|View full text |Cite
|
Sign up to set email alerts
|

Quasi-irreversible inhibition of enolase of Streptococcus mutans by flouride

Abstract: Fluoride at concentrations greater than 0.01 mM was found to be a quasi-irreversible inhibitor of enolase of permeabilized cells of Streptococcus mutans GS-5 and also of isolated yeast enolase. The inhibition appeared to be of the type that has been described for P-ATPases, but was not dependent on added Al3+ or Be2+ ions. Fluoride inhibition of enolase was not reversed by repeatedly washing the permeabilized cells in chilled fluoride-free medium but could be reversed by the product, phosphoenolpyruvate, or by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 9 publications
1
21
0
Order By: Relevance
“…Cells, however, generally exclude aluminum. Another interesting point is reversibility of the fluoride inhibition of enolase by the substrate (2-phosphoglycerate) [Curran et al, 1994], of which the level may increase, when cells are paralyzed by fluoride [Bender et al, 1985]. This intercellular condition may cancel the fluoride inhibition of enolase.…”
Section: Enolase Proton-extruding Atpases and Acidification Of The Cmentioning
confidence: 99%
See 1 more Smart Citation
“…Cells, however, generally exclude aluminum. Another interesting point is reversibility of the fluoride inhibition of enolase by the substrate (2-phosphoglycerate) [Curran et al, 1994], of which the level may increase, when cells are paralyzed by fluoride [Bender et al, 1985]. This intercellular condition may cancel the fluoride inhibition of enolase.…”
Section: Enolase Proton-extruding Atpases and Acidification Of The Cmentioning
confidence: 99%
“…Recently Marquis [1995] expressed his doubt on the view that fluoride inhibition of these enzymes occurs in intact cells in vivo. Reduced activity of enolase and proton-translocating ATPase could not be demonstrated in cells that were permeabilized after fluoride treatment [Marquis, 1990;Curran et al, 1994]. Recent studies suggest that Al 3+ may be necessary for the fluoride inhibition of proton-extruding ATPase Marquis, 1990, 1992].…”
Section: Enolase Proton-extruding Atpases and Acidification Of The Cmentioning
confidence: 99%
“…Preincubation experiments presume that the active compounds bind to the enzymes. It was previously demonstrated that fluoride binds to enolase [Curran et al, 1994] and complexed with Al 3+ to ATPase [Sutton et al, 1987;Sturr and Marquis, 1990].…”
Section: Treatmentsmentioning
confidence: 99%
“…When fluoride enters a cell, the greater part will be bound to cell constituents. Binding of fluoride to enolase and complexed by Al 3+ to ATPase inhibits these enzymes effectively, resulting in a reduction of carbohydrate metabolism [Marquis, 1990;Kaufmann and Bartholmes, 1992;Murphy and Coll, 1992;Curran et al, 1994;Guha-Chowdhury et al, 1997;Marquis et al, 2003]. Inhibition of enolase results in a reduction in the level of phosphoenolpyruvate (PEP), which will subsequently lead to a reduction of glucose uptake by the PEP phosphotransferase system [Kanapka and Hamilton, 1971;Hamilton, 1977;Bender et al, 1986].…”
mentioning
confidence: 99%
“…NaF at 0.5mM induce a bronchorelaxation effect by decrease of bronchial resistances in rats precontracted by acetylmethylcholine analogs and serum concentration of fluoride was within the usual range in blood samples obtained from rats receiving this drug (Gandia et al, 2010). Inhibitory effect of NaF on glycolytic enzyme enolase can be observed in the 10µM range (Curran et al, 1994) on bacteria, which could be of interest in certain lung diseases.…”
Section: Effect Of Fluoride Dose On Bronchial Smooth Musclementioning
confidence: 82%